Eigenvalues of matrices related to the octonions - Serôdio, Rogério (2019)
A pseudo real matrix representation of an octonion, which is based on two real matrix represen- tations of a quaternion, is considered. We study how some operations defined on the octonions change the set of eigenvalues of the matrix obtained if these operations are performed after or before the matrix representation. The established results could be of particular interest to researchers working on estimation algorithms involving such operations.